2016
DOI: 10.1155/2016/7871206
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-Art Report on Alkali Silica Reactivity Mitigation Effectiveness Using Different Types of Fly Ashes

Abstract: Use of fly ash by percent replacement of cement is considered as one of the most economical and effective methods for mitigating alkali-silica reaction (ASR) related distress in the concrete. However, fly ash has been proven to be somewhat variable in its effectiveness in inhibiting alkali-silica reactivity, principally because its composition depends on the coal properties from which it is derived. Typically class C fly ashes are not as efficient as class F ashes due to their higher calcium oxide content. Nev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…Of the same percentage of SCMs replacement, the samples with the low lime content yielded the lower expansion. This observation agreed well with Latifee's report on the correlation between lime content and the expansion of the samples with single SCM, fly ash from many different sources [38]. The higher lime content which reflected the lower content of other beneficial compounds, the higher expansion.…”
Section: Some Chemical Compounds' Ratios and Their Effects On The Expsupporting
confidence: 91%
See 2 more Smart Citations
“…Of the same percentage of SCMs replacement, the samples with the low lime content yielded the lower expansion. This observation agreed well with Latifee's report on the correlation between lime content and the expansion of the samples with single SCM, fly ash from many different sources [38]. The higher lime content which reflected the lower content of other beneficial compounds, the higher expansion.…”
Section: Some Chemical Compounds' Ratios and Their Effects On The Expsupporting
confidence: 91%
“…The reduced expansion suggested that the combination of cement and FA, and aggregates were likely to produce acceptable expansion in concrete in long term [36]. These results agreed well with the others' work for class C high calcium content fly ash [37,38]. This may suggest the benefit of high amount of moderate calcium oxide fly ash in the high volume fly ash concrete (HVFA) when the aggregate was potentially reactive.…”
Section: Accelerated Mortar Bar Test (Ambt)supporting
confidence: 86%
See 1 more Smart Citation
“…The highest expansion was achieved by mortars made with sand S2 and S3 (0.32% and 0.24%), much higher than the allowable limit of 0.1%. Previous investigation revealed that certain hematite aggregate or impure baryte aggregate may also be highly reactive [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In presence of sufficient moisture (e.g., 80% RH), gel absorbs moisture and swells leading to tensile stresses in concrete and eventually resulting in concrete cracks (Mukhopadhyay et al, 2009;Mukhopadhyay & Liu, 2014a). The use of fly ash (primarily class F ash) is the common effective remedial practice to prevent this concrete durability problem (Latifee, 2016). However, there is a major concern that fly ash with required quality and quantity will not be available to prevent ASR in the long term as both fly ash quality and quantity is changing due to the controls imposed by the new emission standards (e.g., the change of coal composition along with applying control measures by thermal power plants to reduce environmental pollution) (Shahzad Baig & Yousaf, 2017).…”
Section: Introductionmentioning
confidence: 99%